Respuesta :

The solution to the system of equations using substitution is: x = 3 and y = -4.

How to Solve a System of Equations Using Substitution?

Given the system of equations:

-7x - 2y = -13 -----> equation 1

x - 2y = 11 -----> equation 2

Rewrite equation 2

x - 2y = 11

x = 11 + 2y

Substitute x = (11 + 2y) into equation 1

-7(11 + 2y) - 2y = -13

-77 - 14y - 2y = -13

-77 - 16y = -13

-16y = -13 + 77

-16y = 64

y = -4

Substitute y = -4 into equation 2

x - 2(-4) = 11

x + 8 = 11

x = 11 - 8

x = 3

Therefore, the solution to the system of equations using substitution is: x = 3 and y = -4.

Learn more about the system of equations on:

https://brainly.com/question/13729904

#SPJ1